Perspectives: Google translate usage / Aishah Musa and Rafidah Amat - Musa, Aishah; Amat, Rafidah (Universiti Teknologi MARA, Kedah, 2023)
The Covid-19 pandemic brought major changes to people’s lives. Education is also highly impacted where online learning is replacing face-to-face learning. Thus, new technologies emerge as required by the new norm. Google provides internet users, especially language learners with new technologies. Google Translate is a machine language translation website provided by Google where it enables internet users to translate over 100 languages. During Open & Distance Learning classes are conducted via online or live streaming; language learners are indirectly exposed to Machine Translation (MT). Google Translate can be accessed via smartphones or computers making it convenient to the learners to use the application since it is easily available online. Thus, this research aims to investigate the students’ perspectives on the usage of Google Translate in language learning. This study was conducted based on the adapted questionnaire used by Riana Devi Susanto (2017) and Alhaisoni & Alhaysony (2017). Based on this study, the findings revealed all the respondents agreed that the use of Google Translate is ethically acceptable regardless of how it is used. Among the advantages of using Google Translate given by the respondents were: to better understand the words that they do not know the meaning of, saves time and makes it easy for them to do their work. Hence, educators should monitor and guide students when they use Google Translate during classroom or online learning.